Semantic Keyword-based Search on Structured Data Sources First COST Action IC1302 International KEYSTONE Conference, IKC 2015, Coimbra, Portugal, September 8-9, 2015. Revised Selected Papers - Cardoso, Jorge; Guerra, Francesco; Houben, Geert-Jan.; Pinto, Alexandre Miguel; Velegrakis, Yannis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the First COST Action IC1302 International KEYSTONE Conference on semantic Keyword-based Search on Structured Data Sources, IKC 2015, held in Coimbra, Portugal, in September 2015. The 13 revised full papers, 3 revised short papers, and 2 invited papers were carefully reviewed and selected from 22 initial submissions. The paper topics cover techniques for keyword search, semantic data management, social Web and social media, information retrieval, benchmarking for search on big data.
Recommending Web Pages using Item-based Collaborative Filtering Approaches -- Processing Keyword Queries under Access Limitations -- Balanced Large Scale Knowledge Matching Using LSH Forest -- Improving css-KNN Classification Performance by Shifts in Training Data. Classification using various ML Methods and Combinations of Key-Phrases and Visual Features -- Mining Workflow Repositories for Improving Fragments Reuse -- Agile DBLP: A Search-based Mobile Application for Structured Digital Libraries -- Support of Part-whole Relations in Query Answering -- Key-Phrases as Means to Estimate Birth and Death Years of Jewish Text Authors -- Professional Collaborative Information Seeking: On Traceability and Creative Sensemaking -- Visualization of Uncertain Information in Tag Clouds -- Multimodal Image Retrieval Based on Keywords and Low-level Image Features -- Toward Optimized Multimodal Concept Indexing -- Semantic URL Analytics to Support Efficient Annotation of Large Scale Web Archives -- Indexing of textual databases based on lexical resources: A case study for Serbian -- Domain-specific modeling: Towards a Food and Drink Gazetteer -- Analysing Entity Context in Multilingual Wikipedia to Support Entity-Centric Retrieval Applications.
Keywords: Computer science; Database management; Information storage and retrieval; Multimedia information systems; User interfaces (Computer systems).; Text processing (Computer science).; Computer Science; Information Storage and Retrieval; Database Management; Information Systems Applications (incl. Internet).; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Document Preparation and Text Processing